First summit of the anti-China coalition: Cornwall G7 highlights BRICS weakness - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2021)
The 2021 G7 Summit of the heads of state and government of the seven leading industrial nations (Germany, France, Italy, Japan, Canada, United States, United Kingdom) will be held in Cornwall, UK, from 11 to 13 June. As host, British Prime Minister Boris Johnson has placed future relations with China at the top of the agenda. That prioritisation is reflected in the guest list: Australia, India, South Korea and South Africa. The Cornwall G7 has been set up to develop a broad alliance against an increasingly aggressive China. The German government tends to play up China's economic significance and risks slipping into an outsider role, enabling a totalitarian state for economic gain.
Keywords: 320